Prevalence and Social Risk Factors of Functional Limitations Among Slum-Dwelling Older Adults: Findings From the Nairobi Urban Health and Demographic Surveillance System. (May 2022) - Gyasi, Razak M.; Aboderin, Isabella; Asiki, Gershim
Objective : In this study, we investigate the patterns and the risk factors of functional limitations in a sample of 1323 slum-dwelling older adults in Kenya who participated in the Nairobi Urban Health and Demographic Surveillance Systems.Methods : We conducted crude and adjusted logistic regression analyses to evaluate the associations.Results : The prevalence of activities of daily living (ADL) and instrumental ADL (IADL) limitations were approximately 5% and 8%, respectively; some 4.5% reported both limitations. Estimates varied significantly between sexes and age ( p < .001). After adjustments, age, female, and Garre ethnic group were associated with ADL and IADL limitations. ADL decline was determined by co-residence (aOR = 0.93, 95% CI = 0.34–0.95), household size (aOR = 1.19, 95% CI = 1.04–1.37) and educational level (aOR = 0.45, 95% CI = 0.05–0.72).Conclusions : Older slum-dwellers in Nairobi experience functional impairments with marked age and sex differences. These findings may encourage salient policy planning and public health interventions to promote healthy aging in informal settlements.